A Comparative Study of Winding Angle Configurations for Improved Crashworthiness in Hybrid Al/CFRP Crash Boxes - Musthafa Akbar; Dyah Kusuma Dewi (Automotive Experiences, 2025)
This study investigates the crashworthiness performance of circular hybrid aluminum/carbon fiber reinforced polymer (Al/CFRP) crash boxes under dynamic axial impact, with particular focus on the influence of winding angle configurations. An explicit finite element model, validated against both experimental and numerical results from the literature, was developed using finite element software. The parametric analysis systematically varied CFRP winding angles from [±15°]₅ to [±85°]₅ in 10° increments and compared the outcomes with single and double cell aluminum crash boxes. Key crashworthiness indicators, including peak crushing force (PCF), mean crushing force (MCF), crushing force efficiency (CFE), stroke efficiency, and folding stability, were evaluated. The results reveal that hybridization significantly enhances load bearing capacity compared to conventional aluminum designs. Intermediate winding angles from 35 to 55 degrees yielded the best balance between PCF reduction, MCF enhancement, and stable progressive folding, with the [±45°]₅ configuration achieving the highest MCF and CFE, while [±35°]₅ minimized PCF. In contrast, winding angles greater than or equal to [±65°]₅ generated excessively high PCF, compromising occupant safety. The findings provide actionable insights for the design of hybrid crash boxes, demonstrating that optimized fiber orientation can advance crashworthiness beyond current aluminum or narrow angle hybrid configurations.